Acidi e basi da Arrhenius a Brønsted: una vicenda con molti protagonisti - Barbarulo, Maria Vittoria; Calascibetta, Franco (Chimica nella Scuola, 2025)
Between the two definitions of acids and bases proposed by S. Arrhenius (1887) and J.N. Brønsted (1923), several important chemists have concentrated their interest and efforts to analyze other relevant properties of these classes of compounds. This work aims to illustrate in particular the role of R. Abegg, P. Pfeiffer, A. Werner and L. Michaelis in the development of a more inclusive definition.